2020
DOI: 10.3390/genes11020203
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Extracellular Vesicles and Its DNA Cargo Secreted During Murine Embryo Development

Abstract: Extracellular vesicles (EVs) are known to transport DNA, but their implications in embryonic implantation are unknown. The aim of this study was to investigate EVs production and secretion by preimplantation embryos and assess their DNA cargo. Murine oocytes and embryos were obtained from six- to eight-week-old females, cultured until E4.5 and analyzed using transmission electron microscopy to examine EVs production. EVs were isolated from E4.5-day conditioned media and quantified by nanoparticle tracking anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 57 publications
0
22
0
Order By: Relevance
“…Besides these cargoes, it is now known that genomic DNA (gDNA) fragments in EVs are transportable between cells, then increase the gDNA-coding mRNA and protein expressions in the recipient cells, eventually affecting the function of recipient cells; for instance, the AT1 receptor DNA in EVs could increase AT1 receptor expression, then stimulate Na + -K + ATPase activity in recipient HEK293 cells [33]. In addition, EVs derived from embryos also contain DNA fragments that represent the full murine genome, which may be useful for embryo chromosomal noninvasive diagnosis [34].…”
Section: General Aspects Of Evsmentioning
confidence: 99%
“…Besides these cargoes, it is now known that genomic DNA (gDNA) fragments in EVs are transportable between cells, then increase the gDNA-coding mRNA and protein expressions in the recipient cells, eventually affecting the function of recipient cells; for instance, the AT1 receptor DNA in EVs could increase AT1 receptor expression, then stimulate Na + -K + ATPase activity in recipient HEK293 cells [33]. In addition, EVs derived from embryos also contain DNA fragments that represent the full murine genome, which may be useful for embryo chromosomal noninvasive diagnosis [34].…”
Section: General Aspects Of Evsmentioning
confidence: 99%
“…Generally, these extracellular vesicle populations consisted of vesicles within 50-200 nm in diameter and the extracellular vesicle population being actively released from preimplantation embryos throughout early development was concluded to be largely exosomal in nature. This is supported by the observation of membrane localized, CD9+ MVBs in fixed murine cell slices from oocyte, cleavage-stage and morula-stage embryos (Simon et al, 2020), including blastocyst trophectodermal cells (Shin et al, 2017) and within trophoblast cells of bovine blastocysts (Mellisho et al, 2017). Uptake of human preimplantation embryoderived extracellular vesicles by primary human endometrial cells has been demonstrated, suggesting extracellular vesicles may be involved in the conceptus-uterus milieu that facilitates the initial attachment and growth of the extraembryonic lineages through the uterine epithelium (Giacomini et al, 2017).…”
Section: Extracellular Vesicles In the Preimplantation Embryonic Secrmentioning
confidence: 78%
“…Extracellular vesicles are released at all stages of human preimplantation development, including cleavage-stage embryos and zygotes (Vyas et al, 2019). Similarly, all stages of porcine (Saadeldin et al, 2014), bovine (Qu et al, 2017;Dissanayake et al, 2020) and mouse (Pallinger et al, 2018;Simon et al, 2020) preimplantation embryos have confirmed extracellular vesicle release. In all cases, the identified vesicles presented the hallmark cupped-shape, double membrane vesicle appearance and amplification of select embryonicspecific mRNA sequences (POU5F1 and NANOG [Giacomini et al, 2017]; Oct4, Sox2, Klf4, c-Myc and Nanog [Saadeldin et al, 2014]) from extracellular vesicleenriched media fractions confirmed the embryonic origin of these vesicles.…”
Section: Extracellular Vesicles In the Preimplantation Embryonic Secrmentioning
confidence: 80%
See 2 more Smart Citations